3D structural framework and constraints on the timing of hydrothermal alteration and ore formation at the Falun Zn-Pb-Cu-(Au-Ag) sulphide deposit, Bergslagen, Sweden - Kampmann, Tobias Christoph (Luleå tekniska universitet, Geovetenskap och miljöteknik, 2015)
The Falun pyritic Zn-Pb-Cu-(Au-Ag) sulphide deposit, situated in the Palaeoproterozoic (1.9–1.8 Ga) Bergslagen lithotectonic unit in the south-western part of the Fennoscandian Shield, is one of the major base and minor precious metal sulphide deposits in Sweden. Host rocks to the deposit as well as the ores and altered rocks were metamorphosed and affected by heterogeneous ductile strain during the Svecokarelian orogeny the total duration of which was 2.0–1.8 Ga. These processes both reworked the mineral assemblages of the original hydrothermal alteration system and reshaped the structural geometry of the deposit, following formation of the ores and the associated hydrothermal alteration.In order to study primary geological and ore-forming processes at Falun, it is necessary firstly to investigate the nature of the tectonothermal modification. In this licentiate thesis, a three-dimensional modelling approach is used in order to evaluate geometric relationships between lithologies at the deposit. This study demonstrates the polyphase character (D1 and D2) of the strong ductile deformation at Falun. The major rock-forming minerals in the silicate alteration rocks are quartz, biotite/phlogopite, cordierite, anthophyllite, chlorite, and minor almandine and andalusite. On the basis of microstructural investigations, it is evident that these minerals grew during distinct periods in the course of the tectonic evolution, with major static grain growth between D1 and D2, and also after D2. Furthermore, the occurrence of F2 sheath folds along steeply south-south-east plunging axes is suggested as a key deformation mechanism, forming cylindrical, rod-shaped ore bodies which pinch out at depth. The sheath folding also accounts for the same stratigraphic level (footwall) on both the eastern and western sides of the massive sulphide ores. A major, sulphide-bearing high-strain zone defines a tectonic boundary at the deposit and bounds the massive sulphide ores to the north.The geological evolution in the Falun area involved ...